2020
DOI: 10.1021/jacs.0c03926
|View full text |Cite
|
Sign up to set email alerts
|

Hydroarylation of Arenes via Reductive Radical-Polar Crossover

Abstract: A photocatalytic system for the dearomative hydroarylation of benzene derivatives has been developed. Using a combination of an organic photoredox catalyst and an amine reductant, this process operates through a reductive radical-polar crossover mechanism where aryl halide reduction triggers a regioselective radical cyclization event, followed by anion formation and quenching to produce a range of complex spirocyclic cyclohexadienes. This light-driven protocol functions at room temperature in a green solvent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…Radical termination through HAT delivers the desired hydroarylation product 1. Evidence supporting this proposal includes a high observed rate of P1* luminescence quenching by the amine base (K SV ≈1700), 17 indicating that radical formation probably occurs through reductive quenching. 17 To probe the nature of radical termination in this process, we conducted a series of isotopic labeling studies.…”
Section: Cluster Synlettmentioning
confidence: 89%
See 1 more Smart Citation
“…Radical termination through HAT delivers the desired hydroarylation product 1. Evidence supporting this proposal includes a high observed rate of P1* luminescence quenching by the amine base (K SV ≈1700), 17 indicating that radical formation probably occurs through reductive quenching. 17 To probe the nature of radical termination in this process, we conducted a series of isotopic labeling studies.…”
Section: Cluster Synlettmentioning
confidence: 89%
“…Evidence supporting this proposal includes a high observed rate of P1* luminescence quenching by the amine base (K SV ≈1700), 17 indicating that radical formation probably occurs through reductive quenching. 17 To probe the nature of radical termination in this process, we conducted a series of isotopic labeling studies. We found that, when the amine reductant was replaced with triethylamine-d 15 , deuterium transfer occurred from the amine to product 1, albeit with moderate fidelity (~1:1 D/H).…”
Section: Cluster Synlettmentioning
confidence: 89%
“…Recently, photoredox‐catalyzed dearomatization reactions have been explored [5] . For example, Jui [5e] and Stephenson [5f] demonstrated that the well‐designed arene substrates were dearomatized through intramolecular carbocyclization. König [5c] and Miyake [5h] reported photoredox‐catalyzed Birch‐type reduction of arenes, which necessitated sacrificial reductants.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, a photochemical approach for the dearomative functionalization of benzene derivatives was developed by Jui's group, which operated through a highly selective radical hydroarylation pathway (Scheme 28). [40k] This established method underwent a reductive radical‐polar crossover mechanism, in which aryl halide reduction triggered a regioselective 5‐ exo ‐trig radical cyclization. Then, the reduction of cyclohexa dienyl radical 132 would generate dienyl anion 133 , followed by protonation and finally producing spirocyclic cyclohexadienes 130 .…”
Section: Intramolecular Cyclizationmentioning
confidence: 99%